The Correlation of Modifiable Risk Factors with Stroke Incidence (JURNAL PROTEKSI KESEHATAN, 2022)
Stroke is the number three killer after heart disease and cancer,but it is the number one cause of disability.  In Indonesia, it is estimated that every year there are 500,000 people affected by stroke and about 125,000 people die, while the rest have minor disabilities and even become severely disabled.  In Indrasari Rengat Hospital, there were 312 patients with stroke and 52 people died from stroke.  This study aims to determine the relationship of modifiable risk factors with the incidence of stroke at the Indrasari Rengat Hospital, Indragiri Hulu Regency in 2020. The design of this study was a cross sectional survey with a total sample of 54 respondents who were hospitalized in the IRNA for neurological diseases and ICU at Indrasari Rengat Hospital starting on the 25th to December 2, 2020, taken using consecutive sampling technique.  The Data collection technique was done by filling out a questionnaire through interviews with patients or families, and through the study of the patient's medical record records. The research instrument was a questionnaire in the form of questions related to modifiable stroke risk factors.  Data analysis in this study was descriptive analysis and bivariate analysis using chi square test.  The results showed that there was a significant relationship between dyslipidemia and the incidence of stroke, with p value = 0.048 (≤ 0.05) .